Outcomes of Ischemic Stroke and Associated Factors Among Elderly Patients With Large-Artery Atherosclerosis: A Hospital-Based Follow-Up Study in China - Wu, Qianqian; Cui, Jingjing; Xie, Yuanli; Wang, Min; Zhang, Huifang; Hu, Xiaofei; Jiang, Fenghua (Frontiers in Neurology, 2021)
Large-artery atherosclerotic (LAA) stroke is the most common subtype of ischemic stroke. However, risk factors for long-term outcomes of LAA stroke in the elderly Chinese population have not been well-described. Therefore, we aimed to assess outcomes and risk factors at 3, 12, and 36 months after LAA stroke onset among stroke patients aged 60 years and older. All consecutive LAA patients aged ≥ 60 years were prospectively recruited from Dongying People's Hospital between January 2016 and December 2018. The clinical features and outcome data at 3, 12, and 36 months after stroke were collected. Differences in outcomes and relationship between outcomes and risk factors were assessed. A total of 1,772 patients were included in our study (61.7% male, 38.3% female). The rates of mortality, recurrence, and dependency were 6.6, 12.6, and 12.6%, respectively, at 3 months after stroke onset. The corresponding rate rose rapidly at 36 months (23.2, 78.7, and 79.7%, respectively). We found the positive predictors associated outcomes at 3, 12, and 36 months after stroke onset. The relative risk (RR) with 95% confidential interval (CI) is 1.06 (1.02–1.10, P = 0.006) at 3 months, 1.06 (1.02–1.10, P = 0.003) at12 months, and 1.10 (1.05–1.15, P < 0.001) at 36 months after stroke onset for age; 1.09 (1.01–1.19, P = 0.029) at 12 months for fasting plasma glucose (FPG) level; 4.25 (2.14–8.43, P < 0.001) at 3 months, 4.95 (2.70–9.10, P < 0.001) at 12 months, and 4.82 (2.25–10.32, P < 0.001) at 36 months for moderate stroke; 7.56 (3.42–16.72, P < 0.001) at 3 months, 11.08 (5.26–23.34, P < 0.001) at 12 months, and 14.30 (4.85–42.11, P < 0.001) at 36 months for severe stroke, compared to mild stroke. Hypersensitive C-reactive protein (hs-CRP) level was an independent risk factor for mortality at different follow-up times, with the RR (95%) of 1.02 (1.01–1.02, P < 0.001) at 3 months, 1.01 (1.00–1.02, P = 0.002) at 12 months. White blood cell count (WBC) level was associated with both stroke recurrence (RR = 1.09, 95%CI: 1.01–1.18, P = 0.023) and dependency (RR = 1.10, 95%CI: 1.02–1.19, P = 0.018) at 3 months. In contrast, a higher level of low-density lipoprotein cholesterol (LDL-C) within the normal range was a protective factor for recurrence and dependency at shorter follow-up times, with the RR (95%) of 0.67 (0.51–0.89, P = 0.005) and 0.67 (0.50–0.88, P = 0.005), respectively. These findings suggest that it is necessary to control the risk factors of LAA to reduce the burden of LAA stroke. Especially, this study provides a new challenge to explore the possibility of lowering LDL-C level for improved stroke prognosis.